Faktor Pencegahan Diare Pada Balita - Pujiati; Marissa Tasya; Setiawan (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2014)
Background: Infants constitute the age group vulnerable to various diseases. Diarrhea has been a major cause of infant death in Indonesia. Knowledge, attitude, and clean and healthy life behavior have some contribution to diarrhea case.Objective: This research aimed at discovering which factor is most significantly associated with the prevention of diarrhea case in infants in the final waste landfill area of Bantar Gebang.Method: This method in this research is analytic with cross-sectional approach, is conducted between October and November 2013 in Bantar Gebang community health center (Puskesmas) with its subjects covering 72 mothers having their children under five. Its bi-variable analysis uses Chi-Square, while its multi-variable analysis uses multiple logistic regression.Result: The study indicated that knowledge (p=0.001), attitude (p=0.001), and clean and healthy life behavior (p=0.009) had some association with diarrhea case. The result of multiple logistic regression test indicated that attitude (OR 23.227) was the factor with most significant association with diarrhea compared to knowledge and behavior.Conclusion: There was an association of knowledge, attitude, and CHLB with diarrhea case in infants.Keywords: Diarrhea case, Knowledge, Attitude, CHLB.